Correction: Electronic conductance and thermopower of single-molecule junctions of oligo(phenyleneethynylene) derivatives. Issue 8 (18th February 2021) - Dekkiche, Hervé; Gemma, Andrea; Tabatabaei, Fatemeh; Batsanov, Andrei S.; Niehaus, Thomas; Gotsmann, Bernd; Bryce, Martin R.
Abstract : Correction for 'Electronic conductance and thermopower of single-molecule junctions of oligo(phenyleneethynylene) derivatives' by Hervé Dekkiche et al., Nanoscale, 2020, 12, 18908–18917, DOI: ; 10.1039/D0NR04413J .